El Excentrico, 1961-06-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 20, 1961 [20 de junio de 1961]. Ano 11, No 17. Cover has a group photograph of a baseball team with headline "Plata's Market All Stars. Santa Clara County Night League."